2009
DOI: 10.1095/biolreprod.109.076869
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Derived Growth Factor C Is Upregulated in Human Uterine Fibroids and Regulates Uterine Smooth Muscle Cell Growth1

Abstract: Leiomyomata uteri (i.e., uterine fibroids) are benign tumors arising from the abnormal growth of uterine smooth muscle cells (SMCs). We show here that the expression of platelet-derived growth factor C (PDGFC) is higher in approximately 80% of uterine fibroids than in adjacent myometrial tissues examined. Increased expression of PDGFC is also observed in fibroid-derived SMCs (fSMCs) relative to myometrial-derived SMCs (mSMCs). Recombinant bioactive PDGFCC homodimer stimulates the growth of fSMCs and mSMCs in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 29 publications
0
29
0
1
Order By: Relevance
“…EGF and PDGF seem to increase DNA synthesis and polyploidization in leiomyoma cells through transient activation of kinase pathways [95–97]. PDGF also modulates the rate of cell proliferation in myometrium and leiomyoma cells [98100]. …”
Section: Pathogenesis Of Uterine Leiomyomamentioning
confidence: 99%
“…EGF and PDGF seem to increase DNA synthesis and polyploidization in leiomyoma cells through transient activation of kinase pathways [95–97]. PDGF also modulates the rate of cell proliferation in myometrium and leiomyoma cells [98100]. …”
Section: Pathogenesis Of Uterine Leiomyomamentioning
confidence: 99%
“…Studies have shown that growth factors can induce proliferation of leiomyoma cells. TGFB1 and PDGF increased leiomyoma cell proliferation in culture [106,107]. Leiomyoma cells grown subcutaneously and treated with PDGF grew larger tumors than untreated mice [107].…”
Section: Regulation Of Growth Factors and Their Receptors By Progestementioning
confidence: 99%
“…TGFB1 and PDGF increased leiomyoma cell proliferation in culture [106,107]. Leiomyoma cells grown subcutaneously and treated with PDGF grew larger tumors than untreated mice [107]. Furthermore, inhibiting PDGFR with lentiviral RNA reduced tumor size of subcutaneous leiomyoma lesions.…”
Section: Regulation Of Growth Factors and Their Receptors By Progestementioning
confidence: 99%
See 1 more Smart Citation
“…As control for transduction efficiency, pLKO-TurboGFP was used. The plasmids were prepared to produce lentiviral particles as previously described [19]. Lentivirus titer determination was performed according to the manufacturer’s instructions (Open Biosystems, Huntsville, AL).…”
Section: Methodsmentioning
confidence: 99%